2020
DOI: 10.26817/16925777.765
|View full text |Cite
|
Sign up to set email alerts
|

Digital Games (Gamification) in Learning and Training: an Approach to Adaptation and Integration in the Classroom

Abstract: This article is the result of the SGI 2174 project. Its objective is to identify how elements, techniques and mechanics game (gamification) have been implemented, as an ICT-mediated learning strategy for learning and training in the education. A systemic literary review of works on the subject is carried out to contextualize and identify methods, techniques, tools and platforms of gamification.  The results make an analysis of the articles reviewed, and describe and describe the technologies and methodologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(24 reference statements)
0
7
0
3
Order By: Relevance
“…To further emphasize, language learning using game-like approaches can be exploited as a potential learning tool to arouse students' motivation, strengthen engagement, and consequently improve their learning quality (Poondej & Lerdpornkulrat, 2016;Yaccob & Yunus, 2019;Ding et al, 2020;Vargas-Macias, Rodriguez-Hernandez, & Sanchez-Saenz, 2020;Pham et al, 2021). For example, Antonaci, Klemke, and Specht (2019) have discussed the deployment of game components in Massive Open Online Course (MOOC) and found that it could increase students' engagement.…”
Section: Literature Review the Application Of Gamified Learning In Es...mentioning
confidence: 99%
See 1 more Smart Citation
“…To further emphasize, language learning using game-like approaches can be exploited as a potential learning tool to arouse students' motivation, strengthen engagement, and consequently improve their learning quality (Poondej & Lerdpornkulrat, 2016;Yaccob & Yunus, 2019;Ding et al, 2020;Vargas-Macias, Rodriguez-Hernandez, & Sanchez-Saenz, 2020;Pham et al, 2021). For example, Antonaci, Klemke, and Specht (2019) have discussed the deployment of game components in Massive Open Online Course (MOOC) and found that it could increase students' engagement.…”
Section: Literature Review the Application Of Gamified Learning In Es...mentioning
confidence: 99%
“…Other game elements or components used in gamification are avatars, scoring, progress bars, rating tables, and ranking displayed (Desnenko et al, 2021). Game-like engaging activities have appealing elements and clear instructions that can motivate students to learn positively (Rafiq et al, 2019b;Vargas-Macias et al, 2020). Besides, with today's technological advancement, ESL teachers can maximize technology use through various available web and application-based software.…”
Section: Gamifying Esl Lessonsmentioning
confidence: 99%
“…De esta forma, le permite un programa personalizado que pueden compartirlo a través de Facebook, generándose una competencia con la comunidad. Otro ejemplo que mencionan Vargas et al (2020) es para el área de turismo, para lo cual se ha aplicado de una estrategia de gamificación ejecutada en Hong Kong, donde se implementó un sitio web parecido a Airbnb obteniéndose una tarjeta SuperHost para usuarios donde registran los comentarios y evaluaciones más importantes.…”
Section: • Gamificación Externaunclassified
“…Fuente: elaboración propia Similarmente, para Vargas et al (2020); Loayza y Vite (2017) señalan que se deben tener definidos los objetivos, la plataforma y las actividades para integrar la gamificación con el área que se desee, como educación, marketing e investigación. Así plantea las siguientes plataformas más utilizadas en el mercado:…”
Section: Autor Año Descripciónunclassified
“…The supportive but challenging character of a game may likely improve motivation and heighten both learning knowledge and skills by allowing for the right difficulty level (for instance, tasks are neither very simple nor very difficult). Thus, these appropriate levels of difficulty ensure that the learner is engaging in activities that are just beyond the student’s knowledge but can be performed with supervision (Vargas-Macías et al 2020 ; Abougalala et al 2020 ). Supervision includes targeted developmental feedback and information to support the learning progress in this gamification task.…”
Section: Introductionmentioning
confidence: 99%